Interleukin-6 Levels and Interleukin-6 rs1800795 Variant in Pediatric Familial Mediterranean Fever: Associations with Clinical Manifestations, Inflammatory Markers, and MEFV Mutation Status - Seyda Dogantan; Yasemin Oyaci; Adem Keskin; Fatima Ceren Tuncel; Sacide Pehlivan (Diagnostics, 2026)
Background/Objectives: Interleukin-6 is a key proinflammatory cytokine involved in the pathophysiology of Familial Mediterranean Fever (FMF). This study aimed to evaluate interleukin-6 levels and the interleukin-6 rs1800795 variant in pediatric FMF participants and to investigate their associations with clinical manifestations, laboratory findings, and Mediterranean fever (MEFV) mutation status. Methods: The research involved 69 pediatric FMF participants and 50 healthy children. Interleukin-6 levels, laboratory findings, and genotype distributions of the interleukin-6 rs1800795 variant were compared between FMF and control groups. Moreover, the relationship between interleukin-6 levels and clinical findings, MEFV mutation status, and laboratory parameters were evaluated in the FMF group. Results: In the FMF group, interleukin-6, serum amyloid-A (SAA), white blood cell count (WBC), neutrophil, C-reactive protein (CRP), and erythrocyte sedimentation rate (ESR) levels were higher compared to the control group. In the FMF group, interleukin-6 levels showed a positive correlation with ISSF score, annual attack frequency, the number of concomitant symptoms, disease duration, SAA, CRP, and ESR. The allele and genotype distribution of the interleukin-6 rs1800795 variant was similar to those in the control and FMF groups. In the FMF group, interleukin-6 values were higher in patients with abdominal pain, fever, chest pain, or arthralgia compared to those without these symptoms. Interleukin-6 levels were higher in both homozygous and compound heterozygous subgroups compared to the heterozygous subgroup. Conclusions: Elevated interleukin-6 levels in symptomatic pediatric FMF patients and those with homozygous or compound heterozygous MEFV mutations suggest that interleukin-6 may reflect both clinical disease severity and MEFV mutation status.